CeIV–GdIII Mixed Oxides as Hosts for ErIII‐Based Upconversion Phosphors. Issue 10 (23rd March 2017) - Sorbello, Cecilia; Gross, Petra; Strassert, Cristian A.; Jobbágy, Matías; Barja, Beatriz C.
Abstract: A family of Er III and Er III –Yb III based nanophosphors, hosted in monophasic oxidic Ce IV –Gd III binary solid solutions, was prepared. The samples were formulated with a constant Er III content as the activator, with the eventual addition of Yb III as a sensitizer. The amorphous Ce0.94− x Gd x Er0.06 (OH)CO3 ⋅H2 O and Ce0.94− x Gd x Er0.05 Yb0.01 (OH)CO3 ⋅H2 O precursors were prepared by following the urea method to obtain monodispersed spheres of tunable size ranging from 30 to 450 nm. After being decomposed at 1273 K under an atmosphere of air, the precursors of 200 nm in diameter evolved into monophasic polycrystalline particles preserving the parent shape and size. The role of the composition of the binary matrices in the emission properties was evaluated for two different excitation wavelengths (976 nm and 780 nm) based on the upconversion (UC) emission spectra and their dependence on the incident power. The yield of the UC process is discussed in the framework of established and novel alternative mechanisms. The number of vacancies and mainly the symmetry of the Er III environment play major roles in the deactivation pathways of the UC emission mechanisms. However, the colours obtained by employing bare Ce IV or Gd III hosts are preserved in the related monophasic Ce IV ‐rich or Gd III ‐rich binary hosts. Abstract : Lift it up : Er III and Er III –Yb III based nanophosphors, hosted in a family of monophasic oxidic Ce IV –Gd III solid solutions, were prepared. The yield of the upconversion (UC) process is discussed in the framework of both established and novel alternative mechanisms. Vacancies and the symmetry of the Er III environment play major roles in the UC emission mechanisms.